HASIL PEMURNIAN ASBUTON LAWELE SEBAGAI BAHAN PADA CAMPURAN BERASPAL UNTUK PERKERASAN JALAN - Furqon Affandi (Direktorat Bina Teknik Jalan dan Jembatan, 2006)
Indonesia only produces asphalt around 650,000 tonnes annually, whilst the need for the constructions and road maintenance is about 1, 2 m illion tones. To meet those needs, Indonesia has imported asphalt from several countries. On the other hand, Indonesia has large deposit of natural asphalt known as Asbuton approximately about 200- 600 million tones which has not been utilized efficiently. Asbuton contain around of 20 % bitu men and 80% mineral. Considering that Indonesia has large deposit of Asbuton and to meet the need of asphalt shortage, new Asbuton product called â€œ Asbuton Murni â€“ Pure Asbuton â€œ has been developed. It is extraction of Lawele Asbuton and processed to be â€œpure â€“ bitumenâ€ containing of less than 1% mineral. â€œAsbuton Murniâ€ is liquid substance like pen bitumen and it can be delivered in drums or bulk, so that is a high affectivity is asphalt hot mix and easily used as other asphalt products. â€œ Asbuton Murniâ€œ product has a good properties as proved from test results such as penetration, softening point, solubility, ductility, loss on heating, high penetratio n index ( + 0. 144) compared with conventional asphalt cement (- 1,127) and perfectly suited for heavy traffic with high temperature like Indonesia. The result of bituminous mixes (hot mix) using â€œA sbuton Murniâ€ showed superiority compared with hot mix using conventional asphalt cement pen grade 60. Another advantage of using Asbuton Murni in hot mix is high stiffness modulus for any temperature test, therefore, it has better spread loading ability from traffic to subgrade and better resistance to permanent deformation as seen in high dynamic stability or less deformation due torepeated loads. Layer thickness for overlay in asphalt hot mix for various design traffic loading is less compared with conventional asphalt pen grade 60, resulting in significant saving. The application in Asphalt Mixing Plant (AMP) is simple because of unrequired additional special equipment, is similar to other mixing process with conventional asphalt pen grade. In short, from the above test results of both bitumen (asphalt) and asphalt mixes, â€œAsbuton Murniâ€ can be able to meet the need of aspha lt shortage nationwide with a better quality